Phylogenetic analysis of the tribe Macropelopiini (Chironomidae: Tanypodinae): adjusting homoplasies - Siri, Augusto (2015)
Macropelopiini is a widely distributed tribe of Tanypodinae, with immature stages inhabiting cool seeps, springs, and small streams. The present study evaluated the monophyly and the supporting synapomorphies within a phylogenetic context for the first time for Macropelopiini. The monophyly and the intergeneric relationships were tested by morphological evidence in a cladistic framework, and the information gained from each homoplastic character was evaluated. The monophyly of Macropelopiini is corroborated through the objective synapomorphy ‘outer fringe decreasing from base to apex ending in small spines’ in the pupa, and the subjective synapomorphies ‘tibial spurs with main teeth and short lateral tooth’ in males and ‘dorsal setae arising from prominent tubercles’ in the pupa. Fittkauimyia Karunakaran, 1969 is excluded from Macropelopiini, Gressitius Sublette & Wirth, 1980 is established as a junior synonym of Alotanypus Roback, 1971, and the new combination Alotanypus antarcticus comb. nov. is proposed. Character combination, mainly through the use of the characters with informative taxonomical value, remains an efficient tool to diagnose the Macropelopiini genera. The new genus Paggipelopia gen. nov. for Paggipelopia spaccesii gen. et sp. nov. is erected and the emendation of the species diagnosis of Wuelkerella toncekensis Añón Suárez & Sublette, 2012 is conducted.